2020
DOI: 10.1371/journal.pone.0243995
|View full text |Cite
|
Sign up to set email alerts
|

The impact of comorbidities on post-operative complications following colorectal cancer surgery

Abstract: Background Colorectal cancer surgery is complex and can result in severe post-operative complications. Optimisation of surgical outcomes requires a thorough understanding of the background complexity and comorbid status of patients. Aim The aim of this study is to determine whether certain pre-existing comorbidities are associated with high grade post-operative complications following colorectal cancer surgery. The study also aims to define the prevalence of demographic, comorbid and surgical features in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 22 publications
2
26
1
Order By: Relevance
“…We found no significant impact of stoma type on prolonging LOS; however, having stoma formation compared to not having stoma formation increases the odds of extending LOS to about 2.5 times. As seen in other published studies, our study also confirms the significance of hypertension, Eastern Cooperative Oncology Group (ECOG) performance, the American Society of Anesthesiologists (ASA) grading assessment, and grade of differentiation on LOS after colorectal surgery (31)(32)(33). Among the demographic features in this study, sex was the only one that significantly influenced prolonged LOS, and this was well described in other studies.…”
Section: Discussionsupporting
confidence: 91%
“…We found no significant impact of stoma type on prolonging LOS; however, having stoma formation compared to not having stoma formation increases the odds of extending LOS to about 2.5 times. As seen in other published studies, our study also confirms the significance of hypertension, Eastern Cooperative Oncology Group (ECOG) performance, the American Society of Anesthesiologists (ASA) grading assessment, and grade of differentiation on LOS after colorectal surgery (31)(32)(33). Among the demographic features in this study, sex was the only one that significantly influenced prolonged LOS, and this was well described in other studies.…”
Section: Discussionsupporting
confidence: 91%
“…The mortality during the first 90 postoperative days due to medical conditions were 61% and 63% of patients in group A and B, respectively. Different clinical parameters have been used to estimate the risk of pancreatic surgery, and here comorbidity comes in as the most important predictor for the postoperative survival [ 18 ]. However, patients who died in the present study did not have an inferior health status compared to those, who passed through the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the first study to estimate the survival impact of COPD (Figure 1) and its severity (measured as number of hospitalizations) before the diagnosis of rectal adenocarcinoma in patients with rectal adenocarcinoma (Figure 2). The reason for this association may be that COPD, especially severe COPD, can increase the risk of more intolerable cardiotoxicity or treatment-related toxicity, decrease the cancer-treatment completion rate, or cause more major complications after treatment [21][22][23]68,69]. Another possible explanation is that smoking may cause more aggressive rectal adenocarcinoma [2], and active and heavy smoking is more common among COPDAE phenotypes [70].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous epidemiologic studies have indicated that smoking is the most critical risk factor for chronic obstructive pulmonary disease (COPD) [13][14][15][16][17][18][19]. In addition, regardless of smoking status, COPD is also an independent risk factor for rectal cancer [20] and is also a strong predictor for intensive care unit admission and mortality after CRC surgery [21,22]; this is as preexisting COPD is an independent risk factor for high-grade complications after treatments [23]. Taken together, both COPD and smoking are independent risk factors or prognostic factors for survival in patients with CRC.…”
Section: Introductionmentioning
confidence: 99%